Relações Públicas: a importância das relações humanas - Endo, Reynaldo Issao [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
This monograph has as objective to study the human relations and the Public Relations in the contemporary time in witch the new technologies of the information got closer to the various existent cultures, but who make of the informative society of the global era, the expansion of the capital and of the culture of the more value. Man kind is backing away from the human relations, because the social interactions in the global world are done by objects such as the television, the internet and the telephone in witch cases the subjectivity and the human contact are traded for the informative quantity, because man kind doesn’t have anymore time to think, reflect and to exchange information. Man kind isolates itself and fills it’s subjective emptiness with the products offered by the neoliberal capitalism. The public relations in the organizations seek the human values created from a complex network of social interactions in all the heterogeneous of the organization. Through the communication the public relations tries to manage the relationships with the dialogical communication, between the public-organization, to harmonize the conflicting differences of the organizational environment. Thus, the public relations has to assume the roll of the information manager, and administrator of the human relations in this new global world, informative and that functions from the capital

Este trabalho tem como objetivo estudar as relações humanas e o relações públicas na contemporaneidade em que as novas tecnologias de informação aproximaram as diversas culturas existentes, mas que fazem da sociedade informativa da era global, a expansão do capital e da cultura da mais valia. O homem se afasta das relações humanas, porque as interações sociais no mundo global são realizadas por meio de objetos como a televisão, a internet e o telefone em que a subjetividade e o contato humano são trocados pela quantidade informativa, porque o homem não tem mais tempo para pensar, refletir e trocar informações. O homem se isola em si mesmo e preenche o seu vazio subjetivo por meio de produtos ofertados pelo capitalismo neoliberal. O relações públicas nas organizações buscam os valores humanos criados a partir de uma complexa rede de interações sociais no todo organizacional heterogêneo. Através da comunicação o relações públicas tenta gerir os relacionamentos por meio da comunicação dialógica entre a organização-público. Para harmonizar as diferenças conflitantes no ambiente organizacional. Assim, o relações públicas tem que assumir o papel de gestor da informação e de gerenciador das relações humanas neste novo mundo global, informativo e movido pelo capital
Keywords: Relações humanas; Relações publicas; Interação social; Comunicação; Tecnologia da informação; Interpersonal relations; Public relations; Social interaction; Communication; Information technology